PERKEMBANGAN SAINS ANAK USIA DINI: EARLY CHILDHOOD SCIENCE DEVELOPMENT - Dwi Agustina, Hilda; Maulidia Hanifa, Hasti (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2023)
Science is not just a collection of facts/knowledge about our world, but there is also a process of observing, note down, analyze, combine with other information, and also make conclusions. Science is an approach to learning that includes the process of finding (inquiry), looking for facts and discuss to increase engagement child so that the child enters the level of ability higher. Playing science in early childhood is one of them activities to develop developmental aspects, and the potential that children have. Science learning train children's ability to recognize various things object symptoms and event symptoms. Children are trained to see, touch, smell, feel, hear and taste. More involvement of the senses In learning, children increasingly understand what is studied. Children gain new know ledge from the results of his sensing with various existing objects surrounding.